Intact acquisition and short-term retention of non-motor procedural learning in Parkinson's Disease - Panouillères, M; Tofaris, G; Brown, P; Jenkinson, N (Public Library of Science, 2016)
Procedural learning is a form of memory where people implicitly acquire a skill through repeated practice. People with Parkinson's disease (PD) have been found to acquire motor adaptation, a form of motor procedural learning, similarly to healthy older adults but they have deficits in long-term retention. A similar pattern of normal learning on initial exposure with a deficit in retention seen on subsequent days has also been seen in mirror-reading, a form of non-motor procedural learning. It is a well-studied fact that disrupting sleep will impair the consolidation of procedural memories. Given the prevalence of sleep disturbances in PD, the lack of retention on following days seen in these studies could simply be a side effect of this well-known symptom of PD. Because of this, we wondered whether people with PD would present with deficits in the short-term retention of a non-motor procedural learning task, when the test of retention was done the same day as the initial exposure. The aim of the present study was then to investigate acquisition and retention in the immediate short term of cognitive procedural learning using the mirror-reading task in people with PD. This task involved two conditions: one where triads of mirror-inverted words were always new that allowed assessing the learning of mirror-reading skill and another one where some of the triads were presented repeatedly during the experiment that allowed assessing the word-specific learning. People with PD both ON and OFF their normal medication were compared to healthy older adults and young adults. Participants were re-tested 50 minutes break after initial exposure to probe for short-term retention. The results of this study show that all groups of participants acquired and retained the two skills (mirror-reading and word-specific) similarly. These results suggest that neither healthy ageing nor the degeneration within the basal ganglia that occurs in PD does affect the mechanisms that underpin the acquisition of these new non-motor procedural learning skills and their short-term memories.